The seven day switch : a novel - Harms, Kelly (Lake Union Publishing, 2021)
"Celeste Mason is the Pinterest stay-at-home supermom of other mothers' nightmares. Despite her all-organic, SunButter-loving, free-range kids, her immaculate home, and her volunteering awards, she still has time to relax with a nice glass of pinot at the end of the day. The only thing that ruins it all is her workaholic, career-obsessed neighbor, who makes no secret of what she thinks of Celeste's life choices every chance she gets. Wendy Charles is a celebrated productivity consultant, columnist, and speaker. On a minute-by-minute schedule, she makes the working-mom hustle look easy. She even spends at least one waking hour a day with her kids. She's not apologizing for a thing. Especially to Celeste, who plays her superior parenting against Wendy whenever she can. Who do Celeste and Wendy think they are? They're about to find out thanks to one freaky week. After a neighborhood potluck and too much sangria, they wake up--um, what?--in each other's bodies. Everything Celeste and Wendy thought they knew about the "other kind of mom" is flipped upside down--along with their messy, complicated, maybe not so different lives."--Provided by publisher.